Taibai Materia Medica: Unofficial ‘Herb Physicians’ in North Western China - Lena Springer (EchoGéo)
In a habitat of mountains in North West China, with few roads and covered in forest and rock, mostly autodidact part-time ‘herb physicians’ gather medicinal plants. Around Mount Taibai, the highest spot in the Han-dominated Eastern half of present-day China, they claim geopolitical legitimacy of their materia medica. Due to its complex climate, the Taibai habitat supplied a complete set of Chinese medical drugs, the unofficial knowledge holders report, and they introduce additional unique local delicacies. Collectively, they enact the picking, cultivation, and storage of the medicinals, and they represent and export them as ‘Taibai materia medica’. Representation has caused changes of the gatherers’ status. One mode is botany-based official regulation of production and pharmaceutical trade. A second mode is cultural heritage preservation based on Daoist lineages.